(2m-n2)-(-3n2+9m)=2m-n2-3n2-9m=-7m-4
化简:(1)(2m-n²)-(-3n²+9m);(2)2x²-4/3(4x-6x²
1个回答
相关问题
-
化简:(1)-5(x^2-3)-2(3x^2+5) (2)2m-3n+[6m-(3m-n)]
-
1 2 1、 —m²- —mn+n² 2、(x+y)²—4x² 3、x³
-
因式分解:4mn^2-4m^2n-n^3 16m^2-4(m+n)^2 (x^2-6)^2-6(x^2-6)+9 x^2
-
化简:(1) -x+(x-3)(2) -1/6(3x-6)+1/3(6-3x)(3) (3m-2n)-(3m-6n+5)
-
已知|m-2|+(3-3n)²=0,化简2x^m-n+1 y^3-6y^m+n x²
-
(m^2-6mn+9n^2)/(3n-m)-(4m^2-9n^2)/(2m-3n) m=-2 n=2008.化简求值
-
化简:(1):4m-7n-2(m-2n).(2):-(x²-2xy-y²)+95x²-2x
-
(m²-6mn+9n²)÷(m-3n)-(4m²-9n²)÷(2m-3n)化简,
-
[(m-n)^2*(n-m)^3]^2/(m-n)^4 [(-x^5)^2]^3/[(x^4)^2/(x^2)^3]
-
如果关于x,y的多项式(n-3)x^(m-1)y^2-2x^(m-2)y+4x^3y(m-2)+2m+3n化简后是一个二